Tailored virtual reality for smart physiotherapy - Postolache, O. (2019)
Remote sensing and Virtual Reality (VR) are technologies that create new development opportunities in the field of serious games with application in physiotherapy. Thus, during a physiotherapy training session expressed by a game around the remote sensing of user body motion provides measurements that can be used for objective evaluation of physical therapy outcomes. In this work is presented a serious game for physiotherapy characterized by Kinect natural user interface and a set of VR games developed in the Unity3D. To provide patient electronic health record, game remote configuration as well as for data presentation for physiotherapist a mobile application was developed. Additionally, several training results expressed by upper limb, neck and spine angles are included in the paper.